Experience-Driven Plasticity of Visual Cortex Limited by Myelin and Nogo Receptor - McGee, Aaron W. (2005)
Monocular deprivation normally alters ocular dominance in the visual cortex only during a postnatal critical period (20 to 32 days postnatal in mice). We find that mutations in the Nogo-66 receptor (NgR) affect cessation of ocular dominance plasticity. In NgR(−/−) mice, plasticity during the critical period is normal, but it continues abnormally such that ocular dominance at 45 or 120 days postnatal is subject to the same plasticity as at juvenile ages. Thus, physiological NgR signaling from myelin-derived Nogo, MAG, and OMgp consolidates the neural circuitry established during experience-dependent plasticity. After pathological trauma, similar NgR signaling limits functional recovery and axonal regeneration.